A Comparative Analysis by Gender and Institution of Technical Accounting Skills Among Polytechnic Students in the Southern Region - MAT KHANIN, UMI NUR ZAHEEDAH; MOHD RAZALI, NUR SYAMIMI (Research and Innovation in Technical and Vocational Education and Training, 2025)
Technical accounting skills play a crucial role in shaping competent graduates who are prepared to face industry challenges. However, issues of mismatch between students’ skill mastery and market demands, as well as the influence of factors such as gender and institutional background on technical learning effectiveness, have received limited attention. This study aims to identify the level of technical accounting skill mastery among accounting students in three core areas which are financial accounting, auditing, and taxation; to compare skill levels based on gender; and to determine differences in skill levels among three TVET institutions: Politeknik Melaka (PMK), Politeknik Merlimau (PMM), and Politeknik Port Dickson (PPD). The study is grounded in four key theories: Human Capital Theory, Skill Acquisition Theory, Gender Schema Theory, and Institutional Theory. A total of 168 fifth- and sixth-semester students from a population of 251 participated in the study. The research employed a quantitative design using a questionnaire adapted from previous studies as the primary instrument. Data were analysed using SPSS software through descriptive and inferential statistics (Mann-Whitney U and Kruskal-Wallis H tests). The findings revealed that students’ technical accounting skills were at a high level, specifically in financial accounting (mean = 4.8, SD = 0.43), taxation (mean = 4.69, SD = 0.59), and auditing (mean = 4.62, SD = 0.64). No significant differences were found between male and female students in all three areas, with p-values > 0.05: financial accounting (p = 0.73), auditing (p = 0.42), and taxation (p = 0.11). However, significant differences were observed among institutions with p-values < 0.05: financial accounting (p < 0.001), auditing (p = 0.021), and taxation (p = 0.004). The study concludes that level of technical accounting skills in education is not solely influenced by individual factors such as gender, but is significantly shaped by institutional factors, thus reinforcing the need for curriculum reforms and more responsive teaching and learning strategies tailored to institutional contexts.